Herbicides Current Research and Case Studies in Use - Price, Andrew J.; Kelton, Jessica A. (IntechOpen, 2013)
Herbicide use is a common component of many weed management strategies in both agricultural and non-crop settings. However, herbicide use practices and recommendations are continuously updated and revised to provide control of ever-changing weed compositions and to preserve efficacy of current weed control options. Herbicides - Current Research and Case Studies in Use provides information about current trends in herbicide use and weed control in different land and aquatic settings as well as case studies in particular weed control situations.